New forms of chromosome polymorphism in Deschampsia Antarctica Desv. from the Argentine Islands of the Maritime Antarctic region - Navrotska, D. O; Twardovska, M. O.; Andreev, I. O.; Parnikoza, I. Yu.; Betekhtin, A. A.; Zahrychuk, O. M.; Drobyk, N. M.; Hasterok, R.; Kunakh, V. A. (Ukrainian Antarctic Journal, 2014)
Cytogenetic analysis of D. antarctica plants from the Argentine Islands of the Maritime Antarctic region was performed. Chromosome number 2n = 26 was determined for most of the samples. New forms of chromosome polymorphism for the species were demonstrated for the first time. In particular, the plants from Darboux Island were found, to have some cells that contained one supernumerary B-chromosome along with 26 chromosomes of a regular set. The plants from Great Yalour Island were determined to be mixoploid – the number of chromosomes ranged from 13 to 39. The occurrence of new and unknown earlier karyotypic forms of D. antarctica might have resulted from increased genome instability due to the extreme environmental conditions in the Argentine Islands region.